Hubungan Pengetahuan Tentang Resiko Paparan DebuDan Perilaku Pencegahan Dengan Gejala Sakit MataPada Pekerja Industri Mebel Di KecamatanNgemplak Boyolali - Indrasto, Destiyanto Bayu; , Kusuma Estu Werdani, SKM., M.Kes (2017)
The furniture industry is starting the process of cutting wood to manufacture a wide range of production has a variety of potential hazards to workers. This study aims to determine the relationship of knowledge about the risk of exposure to dust and prevention behaviors with symptoms of ocular pain in the household furniture industry workers in the district of Boyolali Ngemplak. This research is a quantitative analytic with cross sectional design. Samples were all domestic workers in the furniture industry Boyolali District of Ngemplak totaling 63 people. Data analysis was performed using bivariate analyzes to determine the relationship of independent variables such as knowledge and risk behavior pencegaahan, the dependent variable is the symptoms of eye pain with chi-square test. The results showed that was no relationship between knowledge with symptoms of ocular pain in the Furniture industry workers in District Ngemplak, Boyolali, it shows that the higher a person's knowledge does not necessarily have a safe behavior at work (p> 0.05) and there is a relationship behaviors with symptoms of sore eyes in the furniture industry workers in District Ngemplak, Boyolali (p <0.05).